Family History Is Associated With Recurrent Diverticulitis After an Episode of Diverticulitis Managed Nonoperatively. Issue 7 (July 2020) - Almalki, Turki; Garfinkle, Richard; Kmiotek, Elizabeth; Pelsser, Vincent; Bonaffini, Pietro; Reinhold, Caroline; Yousef, Petro; Morin, Nancy; Vasilevsky, Carol-Ann; Liberman, A. Sender; Boutros, Marylise
Abstract : BACKGROUND: To date, the impact of family history on diverticulitis outcomes has been poorly described. OBJECTIVE: This study aims to evaluate the association between family history and diverticulitis recurrence after an episode of diverticulitis managed nonoperatively. DESIGN: This is a retrospective cohort study with prospective telephone follow-up. SETTINGS: This study was conducted at 2 McGill University-affiliated tertiary care hospitals in Montreal, Canada. PATIENTS: All immunocompetent patients with CT-proven left-sided diverticulitis who were managed nonoperatively from 2007 to 2017 were included. INTERVENTION: A positive family history for diverticulitis, as assessed by a detailed telephone questionnaire, was obtained. MAIN OUTCOME MEASURES: The primary outcome was diverticulitis recurrence occurring >60 days after the index episode. Secondary outcomes included a complicated recurrence and >1 recurrence (ie, re-recurrence). RESULTS: Of the 879 patients identified in the database, 433 completed the telephone questionnaire (response rate: 48.9%). Among them, 173 (40.0%) had a positive family history of diverticulitis and 260 (60.0%) did not. Compared to patients with no family history, patients with family history had a younger median age (59.0 vs 62.0 years, p = 0.020) and a higher incidence of abscess (24.3% vs 3.5%, p < 0.001). After a median follow-up of 40.1 (17.4–65.3) months, patients with a positive family history had a higher cumulative incidence of recurrence (log-rank test: p < 0.001). On Cox regression, a positive family history remained associated with diverticulitis recurrence (HR, 3.74; 95% CI, 2.67–5.24). Among patients with a positive family history, >1 relative with a history of diverticulitis had a higher hazard of recurrence (HR, 2.93; 95% CI, 1.96–4.39) than patients with only 1 relative with a history of diverticulitis. Positive family history was also associated with the development of a complicated recurrence (HR, 8.30; 95% CI, 3.64–18.9) and >1 recurrence (HR, 2.03; 95% CI, 1.13–3.65). LIMITATIONS: This study has the potential for recall and nonresponse bias. CONCLUSION: Patients with a positive family history of diverticulitis are at higher risk for recurrent diverticulitis and complicated recurrences. See Video Abstract at http://links.lww.com/DCR/B215 . LOS ANTECEDENTES FAMILIARES ESTÁN ASOCIADOS CON DIVERTICULITIS RECURRENTE, DESPUÉS DE UN EPISODIO DE DIVERTICULITIS MANEJADA SIN OPERACIÓN: ANTECEDENTES: Hasta la fecha, el impacto de los antecedentes familiares en los resultados de la diverticulitis, ha sido mal descrito. OBJETIVO: Evaluar la asociación entre los antecedentes familiares y la recurrencia de diverticulitis después de un episodio de diverticulitis manejado de forma no operatoria. DISEÑO: Estudio de cohorte retrospectivo con seguimiento telefónico prospectivo. AJUSTES: Dos hospitales de atención terciaria afiliados a la Universidad McGill en Montreal, Canadá. PACIENTES: Todos los pacientes inmunocompetentes con diverticulitis izquierda comprobada por TAC, que fueron manejados sin cirugía desde 2007–2017. INTERVENCIÓN: Una historia familiar positiva para diverticulitis, según lo evaluado por un detallado cuestionario telefónico. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue la recurrencia de diverticulitis ocurriendo > 60 días después del episodio índice. Resultados secundarios incluyeron una recurrencia complicada y >1 recurrencia (es decir, re-recurrencia). RESULTADOS: De los 879 pacientes identificados en la base de datos, 433 completaron el cuestionario telefónico (tasa de respuesta: 48, 9%). Entre ellos, 173 (40.0%) tenían antecedentes familiares positivos de diverticulitis y 260 (60.0%) no tenían. Comparados con los pacientes sin antecedentes familiares, los pacientes con antecedentes familiares tenían una mediana de edad más joven (59.0 vs 62.0 años, p = 0.020) y una mayor incidencia de abscesos (24.3% vs 3.5%, p < 0.001). Después de una mediana de seguimiento de 40.1 (17.4–65.3) meses, los pacientes con antecedentes familiares positivos tuvieron una mayor incidencia acumulada de recurrencia (prueba de log-rank: p < 0.001). En la regresión de Cox, un historial familiar positivo, permaneció asociado con recurrencia de diverticulitis (HR, 3.74; IC 95%, 2.67–5.24). Entre los pacientes con antecedentes familiares positivos, >1 familiar con antecedentes de diverticulitis, tuvieron mayores riesgos de recurrencia (HR, 2.93; IC 95%, 1.96–4.39) en comparación de los pacientes con solo 1 familiar. La historia familiar positiva también se asoció con el desarrollo de una recurrencia complicada (HR, 8.30; IC 95%, 3.64–18.9) y >1 recurrencia (HR, 2.03; IC 95%, 1.13–3.65). LIMITACIONES: Potencial de recuerdo y sesgo de no respuesta. CONCLUSIÓN: Los pacientes con antecedentes familiares positivos de diverticulitis tienen un mayor riesgo para diverticulitis recurrente y recurrencias complicadas. Consulte Video Resumen http://links.lww.com/DCR/B215 . (Traducción—Dr. Fidel Ruiz Healy ) Abstract : Supplemental Digital Content is available in the text.